Family-Friendly Policies, Gender, and Work–Life Balance in the Public Sector. (September 2019) - Feeney, Mary K.; Stritch, Justin M.
Family-friendly policies and culture are important components of creating a healthy work environment and are positively related to work outcomes for public employees and organizations. Furthermore, family-friendly policies and culture are critical mechanisms for supporting the careers and advancement of women in public service and enhancing gender equity in public sector employment. While both policies and culture can facilitate women's participation in the public sector workforce, they may affect men and women differently. Using data from a 2011 study with a nationwide sample of state government employees, we investigate the effects of employee take-up of leave policies, employer supported access to child care, alternative work scheduling, and a culture of family support on work–life balance (WLB). We examine where these variables differ in their effects on WLB among men and women and make specific recommendations to further WLB among women. The results inform the literature on family-friendly policies and culture in public organizations.